Zeitschrift fur Social- und Wirthschaftsgeschichte (Quarterly Journal of Economics, 1893)
Journal Article Zeitschrift für Social- und Wirthschaftsgeschichte Get access The Quarterly Journal of Economics, Volume 7, Issue 2, January 1893, Page 215, https://doi.org/10.1093/qje/7.2.215 Published: 01 January 1893